2010
DOI: 10.1016/j.brainres.2009.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Fos-Tau-LacZ mice reveal sex differences in brainstem c-fos activation in response to mild carbon dioxide exposure

Abstract: There are sex differences in the neurochemistry of brainstem nuclei that participate in the control of breathing, as well as sex differences in respiratory responses to hypoxia. Central chemoreception refers to the detection within the brain of minute changes in carbon dioxide (CO 2 ) levels and the subsequent modulation of breathing. Putative central chemoreceptor sites are widespread and include cells located near the ventral surface of the brainstem in the retrotrapezoid nucleus (RTN), in the medullary midl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
8
0
1
Order By: Relevance
“…Studies by Niblock et al (2012) observed that female RTN neurones are activated after 10% CO 2 exposure, but not after 5% CO 2 exposure, in vivo. On the other hand, male RTN neurones are activated both when exposed to 5% or 10% CO 2 , indicating that there are sex differences in the CO 2 threshold required for the activation of the RTN neurones, with males having a lower threshold (Niblock et al 2010(Niblock et al , 2012, which might explain the differences in CO 2 responses that we found. Also, other chemosensitive regions, such as the locus coeruleus (LC), may be acting on this CO 2 response in a sex-dependent manner.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Studies by Niblock et al (2012) observed that female RTN neurones are activated after 10% CO 2 exposure, but not after 5% CO 2 exposure, in vivo. On the other hand, male RTN neurones are activated both when exposed to 5% or 10% CO 2 , indicating that there are sex differences in the CO 2 threshold required for the activation of the RTN neurones, with males having a lower threshold (Niblock et al 2010(Niblock et al , 2012, which might explain the differences in CO 2 responses that we found. Also, other chemosensitive regions, such as the locus coeruleus (LC), may be acting on this CO 2 response in a sex-dependent manner.…”
Section: Discussionmentioning
confidence: 64%
“…Assessment of the sensitivity of central chemoreceptors to CO 2 in vivo indicates that the CO 2 threshold for the activation of RTN neurones is higher in females than in male adult mice (Niblock et al . , ). Studies by Niblock et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in healthy human subjects using mechanical ventilation to induce hypocapnia have demonstrated that the apneic threshold is <5 mmHg below the normal, eupneic PaCO 2 (157, 227). And the addition of very small amounts of inspired CO 2 to sleeping subjects who exhibit periodic breathing stabilizes breathing (17, 191). Thus, central and peripheral CO 2 sensitivity are very important in determining apnea and periodic breathing (10, 108, 264).…”
Section: The Function Of Central Chemoreceptorsmentioning
confidence: 99%
“…It seems that some level of CO 2 is needed to maintain the normal interactions among the different types of respiratory neurons and to provide a ‘drive’ to the system, at least in NREM sleep and anesthesia. This has been demonstrated dramatically by Bruce Lindsey and his colleagues (191) using their unique approach in decerebrate, ventilated cats with simultaneous multi-array recording of neurons each with individual electrode depth adjustment in the regions of the medullary raphe nuclei, the ventral respiratory column, and the pontine respiratory group (Nuding et al, 2005 abst). Hyperventilation decreased end-tidal PCO 2 from 29 to 10 mm Hg and abolished rhythmic phrenic nerve activity.…”
Section: The Function Of Central Chemoreceptorsmentioning
confidence: 99%